FAKTOR FAKTOR YANG MEMPENGARUHI LITERASI KEUANGAN ( Studi Pada Mahasiswa Fakultas Ekonomi Universitas Malahayati Bandar Lampung ) - Alenda, Ulfa; Listyaningsih, Erna; Nurbaiti, Nurbaiti (Universitas Malahayati, 2021)
This study aims to analyze the factors that influnce student's financial literacy using variables learning in college and family financial education, parental socioeconomic status, number of University Credit Unit taken, and residence status. The population in this study was 134 and the sample in this study was 134 people using saturated sample techniques. This study uses multiple linear regression analysis to test hypotheses. The results of this study indicate that learning in college and family financial education, and number of University Credit Unit taken have a positive and significant effect on financial literacy. Whereas parental socioeconomic status and residence status do not affect financial literacy.Keywords: Financial literacy, learning in college, family financial education, parental socioeconomic status, the number of University Credit Unit taken, and the residence status